LATARBELAKANG KATA-KATA PINJAMAN BAHASA ASING DI DALAM BAHASA TAMIL (THE BACKGROUND OF BORROW-WORDS IN TAMIL LANGUAGE) - Subramani Selvan, Pushpa Rani; Ramasamy, Mohana Dass (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2016)
Language plays an important role in human life. It has its own privileges, and is able to distinguish between humans and other species. Human privilege is characterized by the uniqueness that is rarely seen in other species, the ability to pass on information to others. Language is not a living thing, it serves as instrument for every human activity. As languages ​​are constantly changing and evolving, they were constantly on the need of increasing number of vocabulary for progressive communication. This flexible feature leads to lending and borrowing processes between languages. Although the Tamil language is often said to have a unique long surviving history, it also faced similar situations, borrowing vocabulary from foreign languages. This has become important to remain competitive and remain in line with the current demands. This paper examines the different types of loanwords that were adopted in Tamil, just to meet the mentioned needs. Bahasa memainkan peranan yang penting dalam kehidupan manusia. Ia memiliki keistimewaan tersendiri, dan berupaya membezakan manusia dengan spesis-spesis lain. Keistimewaan manusia terserlah dengan adanya keunikan tersendiri yang jarang dilihat pada spesis-spesis lain, iaitu, keupayaan untuk menyampaikan maklumat kepada orang lain (Bloomfield 1933). Bahasa bukan sesuatu benda hidup yang kekal, malahan, ia adalah sesuatu aktiviti yang dilakukan oleh manusia (Jespersen 1964). Bahasa sering berubah dan berevolusi. Keadaan ini membawa kepada pertambahan kosa kata di dalamnya apabila diperlukan. Ciri fleksikal ini membawa kepada proses pinjam dan meminjam berlaku diantara bahasa. Sungguhpun Bahasa Tamil sering dikatakan mempunyai sejarah klasik yang unik, ia turut berhadapan dengan keadaan sedemikian, peminjaman kosa kata daripada bahasa asing untuk terus bersaing dan kekal bersesuaian dengan kehendakan semasa. Kertas kerja ini mengkaji pelbagai jenis kata pinjaman yang diterima pakai dalam bahasa Tamil.